(untitled) - Koolman, Jan (Stuttgart, 2005)
Totally revised and expanded, the Color Atlas of Biochemistry presents the fundamentals of human and mammalian biochemistry on 215 color plates." "Alongside a short introduction to chemistry and the "classic topics" of biochemistry, the 2nd edition covers new approaches and aspects in biochemistry, such as links between chemical structure and biological function or pathways for information transfer, as well as recent developments and discoveries, such as the structures of many new important molecules." "This book is ideal for students of medicine and biochemistry and a valuable source of reference for practitioners
Keywords: Hóa sinh,Biochemistry